PTU-096 The use of commercial interferon-γ release assays to screen for mycobacterial infection in inflammatory bowel disease patients initiating anti-TNF agents. (28th May 2012) - Greveson, K; Murray, C; Goodhand, J; Cropley, I; Murthy, S; Hamilton, M; Lipman, M
Abstract : Introduction: Two commercial Interferon Gamma release assays (IGRA) are approved in the UK by NICE and US FDA to detect M tuberculosis (Mtb) infection. The T-Spot.TB (TSTB) and Quanitferon Gold In-tube (QFGIT) use different test platforms, with the potential for slightly different results when used in clinical practice. Since 2008, we have used a standard IGRA-based assessment for Mtb infection in inflammatory bowel disease (IBD) patients. Initially this involved TSTB but in December 2010, switched to QFGIT. Here we review the performance of these assays within our protocol. Methods: We prospectively screened 148 adult IBD patients considered for anti-TNfα agents with symptom review, chest radiograph and IGRA. Between October 2008 and November 2010, 91 patients were tested with TSTB, and between December 2010 and November 2011, 57 with QFGIT. IGRA results were reported as positive, negative or indeterminate. Positive and indeterminate results were referred to TB services. Results: All subjects had normal chest radiographs and a negative clinical assessment. Overall 82% (121/148) subjects tested were BCG vaccinated and 13% (19/148) had risk factors for Mtb. 74% (109/148) were taking immunomodulators. 98% (89/91) patients in the TSTB group had an unequivocal result [1% (1/91) positive: 97% (88/91) negative], and 1% (1/91) had an indeterminate result, compared with 86% unequivocal [0% positive/86% negative] and 14% (8/57) indeterminate in the QFGIT group, respectively (p=0.002). 12% indeterminate results occurred in subjects taking immunosuppression. 85% (126/148) of the anti-TNFα naïve group have subsequently received treatment with either infliximab or adalimumab. None have gone on to develop tuberculosis. Median follow-up from start of therapy in the TSTB group is 21 months (IQR 15–26 months); and that of the QFGIT group 7 months (IQR 4–9). Conclusion: We find little evidence for Mtb infection within our IBD population. To date none have developed active TB after starting anti-TNFα therapy. Given the reasonable median follow-up (21 months for TSTB and 7 months for QFGIT) compared to the reported time of onset of active TB following anti-TNFα agents (<3 months), our data provide some reassurance that we have not missed LTBI using our assessment. There appears to be a higher frequency of indeterminate results using QFGIT. As this is found almost exclusively in those on immunosuppressive agents, we suggest that IBD services need to understand the characteristics of the IGRA used within their population and the implications of this for management. Competing interests: None declared.